Higher Education Financing in Nepal - Baral, Keshar J. (Journal of Nepalese Business Studies, 2008)
National policy on the financing of higher education is to recover the recurrent costs and shift the burden of higher education to the private sector. This paper, using the financial data pub-lished by University Grants Commission (UGC) and extracted from the financial statements of Pokhara University (POKU), attempts to analyze the financing pattern of higher education in Nepal. In gen- eral, it analyzes the overall financing pattern of higher education in Nepal and in particular of POKU during the last eight fiscal years (FY 1999 through 2006). This concludes that the level of budget for higher education in Nepal is relatively low and not enough to bring up the accessibility of qualitative higher education. Moreover, it concludes that government grants-both administrative and development, provided to the universities are not consistent during the study period. The Journal of Nepalese Business Studies Vol. IV, No. 1 (2007) pp. 1-9